Phase transformations in an ultralight BCC Mg alloy during anisothermal ageing. (15th October 2022) - Xin, Tongzheng; Tang, Song; Ji, Fan; Cui, Luqing; He, Binbin; Lin, Xin; Tian, Xiaolin; Hou, Hua; Zhao, Yuhong; Ferry, Michael
Abstract: Mg-Li-Al alloys with a body-centred cubic (BCC) structure can exhibit exceptional specific strengths in combination with excellent ductility and corrosion resistance. In general, the strength of these alloys is very sensitive to the processing temperature due to the occurrence of various phase transformations. Although different phases have been identified in these alloys, their corresponding transformation mechanisms and unique role played in controlling the mechanical properties have never been studied in depth. In this work, we identified the phase transformation sequence by in-situ synchrotron X-ray diffraction. Moreover, we investigated the evolution of precipitation and their morphology using transmission and scanning electron microscopy, together with simulations based on the phase field modelling and first-principles calculations. Phase transformation sequence of Al-rich zone → θ (D03 − Mg3 Al) → AlLi was confirmed during anisothermal ageing. A braided structure resulting from spinodal decomposition was found to be the optimized microstructure for achieving the peak strength. Nanocrystalline α-Mg phase at the interface between θ and the matrix was identified as the main reason for softening in the alloy. The core-shell model for θ → AlLi transformation is observed and verified. Our findings deepen the understanding of BCC Mg-Li-Al alloys and pave a pathway to develop new generation of ultralight alloys with stronger strength and better stability. Graphical abstract: Image, graphical abstract